2021
DOI: 10.3390/app11209666
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Atypical Pheochromocytomas with Correlative MRI and Planar/Hybrid Radionuclide Imaging: A Preliminary Study

Abstract: Pheochromocytomas may show atypical imaging findings leading to diagnostic pitfalls. We correlated the results of magnetic resonance imaging (MRI) with those of radionuclide studies in patients with pheochromocytomas. T2-weighted (-w), T1-w chemical-shift and T1-w dynamic contrast enhanced (DCE) MRI sequences were evaluated to assess tumor structure. 131Iodine metaiodobenzylguanidine (MIBG) scintigraphy, 18fluoro (F) deoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) or FDG PET/MRI we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Furthermore, in some pioneering studies, scholars have been able to identify the adrenal tumour parenchyma and cystic necrosis components by using positron emission tomography (PET)-CT and dynamic contrast enhanced (DCE) techniques. In pheochromocytoma, especially that presenting with cystic components, the active areas of tumour metabolism are concentrated in the relatively thin cyst wall of the tumour (30). This finding can effectively be used to differentiate pheochromocytoma from other benign cystic masses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in some pioneering studies, scholars have been able to identify the adrenal tumour parenchyma and cystic necrosis components by using positron emission tomography (PET)-CT and dynamic contrast enhanced (DCE) techniques. In pheochromocytoma, especially that presenting with cystic components, the active areas of tumour metabolism are concentrated in the relatively thin cyst wall of the tumour (30). This finding can effectively be used to differentiate pheochromocytoma from other benign cystic masses.…”
Section: Discussionmentioning
confidence: 99%
“…In case of atypical pheochromocytomas that undergo cystic degeneration, integrating MRI findings with those of correlative planar/hybrid radionuclide images should be considered as tumour accumulation of MIBG and/or FDG in the residual solid tissue or in the peripheral tumour rim may help to classify properly these lesions and disclose their real nature [ 37 , 38 ].…”
Section: Diagnosis and Stagingmentioning
confidence: 99%
“…In oligo-metastatic PPGLs, locoregional approaches including radiotherapy, stereotaxic surgery, radiofrequency ablation or cryoablation, percutaneous ethanol injection, may represent reasonable options for local control and managing mass effect symptoms or hormone-related symptoms [ 11 , 21 , 37 , 118 , 119 , 120 ]. However, indications must be individualized and discussed within multidisciplinary team as no prospective data are available.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Diagnosing this type of pheochromocytoma is quite challenging, as we cannot rely on anatomical imaging modalities (MRI and CT). Accordingly, a recent study showed that 78% of pheochromocytomas with atypical anatomical imaging features (on CT or MRI) were totally or predominantly cystic [42]. In this situation, the most accurate way to assess these lesions is using a variety of functional imaging modalities like iodine metaiodobenzylguanidine (MIBG) scintigraphy, 18 fluoro (F) deoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT), 18 FDG-PET/MRI, 18 F-Fluoro-dihydroxyphenylalanine ( 18 F-DOPA) PET/CT, and somatostatin receptor (SSTR) agonist-based PET/CT imaging [42,43].…”
Section: Question 4: Which Adrenal Cyst Subtypes Exist?mentioning
confidence: 99%
“…Accordingly, a recent study showed that 78% of pheochromocytomas with atypical anatomical imaging features (on CT or MRI) were totally or predominantly cystic [42]. In this situation, the most accurate way to assess these lesions is using a variety of functional imaging modalities like iodine metaiodobenzylguanidine (MIBG) scintigraphy, 18 fluoro (F) deoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT), 18 FDG-PET/MRI, 18 F-Fluoro-dihydroxyphenylalanine ( 18 F-DOPA) PET/CT, and somatostatin receptor (SSTR) agonist-based PET/CT imaging [42,43]. It was demonstrated that even completely cystic pheochromocytomas captivate radiotracers like MIBG and FDG in the peripheral tumour rim or in residual tumour tissue [42].…”
Section: Question 4: Which Adrenal Cyst Subtypes Exist?mentioning
confidence: 99%